Recent research status of Bactrocera dorsalis: Insights from resistance mechanisms and population structure. Issue 3 (22nd July 2019) - Wei, Dan‐Dan; He, Wang; Lang, Ning; Miao, Ze‐Qing; Xiao, Lin‐Fan; Dou, Wei; Wang, Jin‐Jun
Abstract: Bactrocera dorsalis (Hendel) is considered to be a highly invasive and destructive agricultural pest due to its strong dispersal and adaptive capacity. Rapid development of insecticide resistance poses a serious threat to the sustainable control of this pest. Here, the resistance mechanisms and invasion pathways of this fly are outlined for a better understanding of the resistance‐gene flow pattern and invasion routes. We believe this microreview will provide a glimpse of the native regions, spread and management of resistance, and guide future work on these important topics. Abstract : South‐East Asia is the potential source areas original location for Bactrocera dorsalis, and its distribution in China was a result of multiple invasions from South‐East Asia and coastal region of China.